STUDY OF THE EFFECT OF TOFU DUMP AND OKRA FLOUR SUBSTITUTION ON THE CONTENT OFSTUDY OF THE EFFECT OF TOFU DUMP AND OKRA FLOUR SUBSTITUTION ON THE CONTENT OF PROTEIN, FIBER, F PROTEIN, FIBER, FAT, CARBOHYDRATE, AND ORGANOLEPTIC PROPERTIES OF CHICKEN NUGGET - Jessica Novanti Kurniawan; Yuyun Yuniati; Retnani Rahmiati (RADJA PUBLIKA, 2026)
The use of alternative plant-based food ingredients in processed meat products has the potential to increase nutritional value while diversifying raw materials . This study aims to analyze the effect of tofu dregs and okra flour substitution on the chemical and organoleptic characteristics of chicken nuggets and determine the best formulation based on effectiveness testing. The study was conducted as a laboratory experiment using a Completely Randomized Design (CRD) with four levels of substitution of tofu dregs and okra flour (0%, 25%, 50%, and 75%), each repeated three times. The chemical parameters analyzed included protein (Kjeldahl), fat (Soxhlet), fiber (gravimetric), and carbohydrate (by difference) levels . Organoleptic tests were conducted using the hedonic method by 20 trained panelists on color, aroma, taste, and texture attributes. Chemical data were analyzed using ANOVA at the 5% level and further tests, while organoleptic data were analyzed using the Friedman test. The results showed that the substitution of tofu dregs and okra flour significantly affected the chemical and organoleptic characteristics of chicken nuggets. Increasing the substitution level significantly increased protein and fiber levels and decreased fat and carbohydrate levels, but decreased the level of panelist acceptance of sensory attributes. Based on the effectiveness test, the treatment with the highest substitution showed the best total effectiveness value due to the superiority of nutritional parameters, although the control treatment had the highest organoleptic acceptance. Thus, the substitution of tofu dregs and okra flour has the potential to be used to increase the nutritional value of chicken nuggets, while still paying attention to formulation optimization to maintain the sensory quality of the product.